Determinants of Firm Value Through Dividend Policy, Leverage, Profitability, and Financial Risk in the Perspective of Strategic Financial Management - Wetri Efita; Hendra Kasman; Beno Jange; David Humala Sitorus (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Firm value remains one of the most important indicators used by investors to assess corporate performance and long-term sustainability. This study investigates the influence of dividend policy, leverage, profitability, and financial risk on firm value from the perspective of strategic financial management. The research adopts a quantitative explanatory approach using secondary data obtained from annual reports of manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A total of 100 observations were selected through purposive sampling. Data analysis was conducted using Statistical Package for the Social Sciences (SPSS) version 27, including validity tests, reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-tests, and F-tests. The findings reveal that dividend policy has a positive and significant effect on firm value, indicating that consistent dividend payments enhance investor confidence. Leverage demonstrates a significant negative effect, suggesting that excessive debt utilization increases financial vulnerability and lowers market valuation. Profitability exerts the strongest positive influence on firm value, reflecting the importance of earnings generation in attracting investment. Financial risk negatively affects firm value due to increased uncertainty and perceived investment risk. Simultaneously, all independent variables significantly explain variations in firm value. The study concludes that strategic financial management should emphasize balanced dividend distribution, prudent debt management, sustainable profitability improvement, and effective risk control to maximize firm value. A limitation of this research lies in its focus on manufacturing companies and a limited observation period, which may restrict generalizability to other industries and economic environments.